Effect of multi‐walled iron‐filled carbon nanotubes on ATPase activity and superprecipitation of natural actomyosin. Issue 2 (13th March 2013) - Andreichenko, K.; Shelyuk, O.; Prylutska, S.; Nuryshchenko, N.; Bogutska, K.; Prylutskyy, Y.; Ritter, U.; Scharff, P.
Abstract The dependence of actomyosin superprecipitation and Ca2+, Mg2+‐ and K+‐ATPase activity inhibition on the concentration of multi‐walled iron‐filled carbon nanotubes (Fe‐MWCNTs) was investigated. For the superprecipitation of actomyosin, a biphasic effect of Fe‐MWCNTs was found. Namely, at low concentrations (10–9 mg/ml) the superprecipitation was activated, while at high concentrations (10–7 and 10–5 mg/ml) its activity was inhibited.